Peningkatan Pengetahuan CPPB-IRT pada Kelompok Jamu Gendong di Desa Beji Kecamatan Bojongsari Purbalingga: Improving Knowledge of CPPB-IRT in the Jamu Gendong Group in Beji Village, Bojongsari District, Purbalingga - Genatrika, Erza; Arofah, Rifka Utami; Febrina, Dina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The limited understanding of the jamu gendong group regarding food safety standards, despite this industry's significant economic potential. This community service activity involves providing training to increase the jamu gendong group's knowledge in Beji Village, Bojongsari District, Purbalingga, on Good Food Production Practices for Home Industries (CPPB-IRT). The training was delivered offline over three hours, divided into four sessions: pre-test, material presentation, practice/discussion, and post-test. Knowledge measurement was carried out by comparing questionnaire scores on the pre-test and post-test using a Likert scale. This training significantly increased knowledge among 45 participants, predominantly women (100%) and adults (80%). The average pre-test score was low (1.27-2.00), then increased in the post-test (3.64-4.00). The highest increase occurred in the item "SPP-IRT Requirements" with a score increase of 2.44. The training was deemed highly effective based on positive participant perceptions: 100% reported that it met their needs and improved their knowledge. In conclusion, the program successfully increased participants' knowledge of CPPB-IRT and is expected to be sustainable.